Urban development and urban ills - Mills, Edwin S.; Mitra, Arup, 1964- (New Delhi : Commonwealth Publishers, 1997)
Deals with seminal debate on city growth in developing countries in general and India in particular.
Includes bibliographical references (p. [104]-111) and index.
Keywords: Urbanization -- India; Cities and towns -- India; Slums -- India; Poor -- India